2021
DOI: 10.24018/ejmed.2021.3.3.880
|View full text |Cite
|
Sign up to set email alerts
|

Side Effect Profile of COVID-19 Vaccine among Health Workers in a Tertiary Health Institution in South-South Nigeria

Abstract: Background: Side effect following vaccination usually ranges from mild to moderate and occasionally severe in a small proportion of people. Covid-19 vaccine is no exception as side effects have been reported which are mostly mild to moderate and transient. The chances of any of these side effect following vaccination differ according to the specific COVID-19 vaccine. Objective: To determine the side effect profile of the Health workers that received the COVID-19 vaccination in the Federal Medical Centre,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
2
5
1
Order By: Relevance
“…AE severity in our study was mild to moderate, which is consistent with practically all prior investigations of AstraZeneca COVID-19 vaccine [12,20,23,25,29]. For instance, none of the AstraZeneca COVID-19 vaccine recipients in Nepal developed severe adverse events or required long-term hospitalization and no deaths were reported within a week [20].…”
Section: Plos Global Public Healthsupporting
confidence: 91%
See 4 more Smart Citations
“…AE severity in our study was mild to moderate, which is consistent with practically all prior investigations of AstraZeneca COVID-19 vaccine [12,20,23,25,29]. For instance, none of the AstraZeneca COVID-19 vaccine recipients in Nepal developed severe adverse events or required long-term hospitalization and no deaths were reported within a week [20].…”
Section: Plos Global Public Healthsupporting
confidence: 91%
“…The incidence of adverse events in this study is far lower than 79.4% and 90.9% reported for the same vaccine in Nepal and Korea respectively [20,25]. Other studies found 93.5% incidence in Afghanistan and 90.1% in South-south Nigeria [12,23]. A possible explanation for the wide disparity in the incidence of adverse events in these studies compared to ours is that all of these studies were carried out among health care workers whereas, ours was carried out among the general population.…”
Section: Plos Global Public Healthcontrasting
confidence: 72%
See 3 more Smart Citations